Penyuluhan dan Alih Teknologi Penggunaan Meja Smart Conveyor sebagai Alat Bantu Physical Distancing untuk UMKM PT Mitra Indonesia - Nugroho, Oki Widhi; Montororing, Yuri Delano Regent; Tambunan, Erwin Barita Maniur (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Micro, Small and Medium Enterprises Retail PT Mitra Indonesia is a trading retail business that carries out trading activities for the main consumption needs of the community. Based on interviews and observations at Micro, Small and Medium Enterprises Retail PT. Indonesian Partners, Their business operations have been disrupted due to the issuance of a Government Regulation on Large-Scale Social Restrictions and the government's call for physical distancing. So far, Micro, Small and Medium Enterprises Retail PT. Mitra Indonesia has a face-to-face service flow with customers, where when the Large-Scale Social Restrictions and physical distancing rules are implemented, the service flow will be disrupted. The stages that will be carried out related to the implementation of Community Service include the Observation & Focus Group Discussion stages (Phase 1). At this stage, a direct observation is carried out to analyze the situation and conditions of partners regarding the need for guidance and transfer of technology that is useful for training media and to determine the type of material to be disseminated so as to result in improvements to the process of business activities. The focus of counseling will focus on business operations that are adaptive and compliant with Government Regulations concerning Large-Scale Social Restrictions and government calls for physical distancing. The second is counseling regarding the use of smart conveyor technology for new business operations. Stage 2, the next is the transfer of technology using the smart conveyor table. Consisting of Activity Preparation Stages in the form of making a smart conveyor table. The process of making a smart conveyor table follows phase 1 of analysis, phase 2 of product design, phase 3 of assembly, and phase 4 of trial.The Implementation Stage (Phase 3) is in the form of counseling on new business operational models and coaching on how to use the smart conveyor table. Counseling regarding the new business operational model is carried out on the basis of Government Regulations concerning Large-Scale Social Restrictions and Calls for Physical Distancing, so that there is a need for adaptation to business operations. Adaptation of new business operations is proposed by changing the method of transactions into 2 types. The first is online, and the second is offline. The last stage is Technology Transfer and Evaluation (Stage 4). At this stage the implementation of activities is evaluated by the team and see what obstacles and problems that arise in the field. Then an evaluation is carried out if obstacles and problems do arise to then find a solution so that the activity continues properly as expected.